2022
DOI: 10.3390/ijerph191710863
|View full text |Cite
|
Sign up to set email alerts
|

Grading Nursing Care Study in Integrated Medical and Nursing Care Institution Based on Two-Stage Gray Synthetic Clustering Model under Social Network Context

Abstract: Establishing a scientific and sustainable grading nursing care evaluation system is the key to realizing the rational distribution of medical and nursing resources in the combined medical and nursing care services. This study establishes a grading nursing care index system for medical and nursing institutions from both medical and nursing aspects, and proposes a grading nursing care evaluation model based on a combination of interval-valued intuitionistic fuzzy entropy and a two- stage gray synthetic clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Community home elderly care services have become the focus of the development of China's elderly care service industry. Integrate medical and health resources and endowment service resources, and provide continuous and integrated services such as hospitalization, rehabilitation care, and stable life care for the chronically ill elderly through convenient and professional services ( 5 ). For older adults with chronic conditions, family physician services and appropriate medical care services, such as home care and day care, can be provided to older adults, or medical services can be provided through community-based primary care ( 6 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Community home elderly care services have become the focus of the development of China's elderly care service industry. Integrate medical and health resources and endowment service resources, and provide continuous and integrated services such as hospitalization, rehabilitation care, and stable life care for the chronically ill elderly through convenient and professional services ( 5 ). For older adults with chronic conditions, family physician services and appropriate medical care services, such as home care and day care, can be provided to older adults, or medical services can be provided through community-based primary care ( 6 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessing the service level of medical institutions is vital to enhancing patient care and promoting quality improvements ( Lin, Shih & Ho, 2023 ; Xu & Zhang, 2022 ). The conventional approach to assigning grades to medical institutions based on assessment scores involves using mainstream Software called a SaaS system.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies also found that the quality of nursing personnel in some elderly care institutions is generally low, and the service attitudes need to be improved [ 24 25 ]. Most of the existing medical-elderly care integrated institutions are mainly elderly care institutions with embedded medical institutions, and the career development of doctors is highly restricted [ 26 27 ]. Therefore, there are difficulties in forming professional medical teams, and the technical level of doctors could be higher [ 28 ].…”
Section: Introductionmentioning
confidence: 99%